Pengaruh Resiliensi terhadap Psychological Well-Being Pada Mahasiswa Program Pertukaran Mahasiswa Merdeka (PMM2) Di Institut Kesehatan Helvetia Tahun 2022 - Tarigan , Rahmawati; Chairunisa , Milna; Afriani , Miskah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
When a change occurs unexpectedly, a person must adapt to unpleasant conditions and find a way out of the problems experienced. These changes certainly affect the psychological condition of students who move from one province to another and temporarily change their place of study. This study was conducted to obtain a picture of the resilience and psychological well-being of students in the Independent Student Exchange Program (PMM2) at the Helvetia Health Institute in 2022 in facing different situations, such as different lecture systems and cultures from their home areas, and whether there is an influence between resilience and the psychological well-being of students in the Independent Student Exchange Program (PMM2) at the Helvetia Health Institute in 2022. This study uses a quantitative approach. The research participants were 30 Independent Student Exchange Program (PMM2) students. Data was collected using two scales, namely the resilience and psychological well-being questionnaires. Data analysis was carried out using a simple linear regression test.